Depressive Symptoms and Their Relation to Age and Chronic Diseases Among Middle-Aged and Older Adults in Rural South Africa. (22nd June 2018) - Geldsetzer, Pascal; Vaikath, Maria; Wagner, Ryan; Rohr, Julia K; Montana, Livia; Gómez-Olivé, Francesc X; Rosenberg, Molly S; Manne-Goehler, Jennifer; Mateen, Farrah J; Payne, Collin F; Kahn, Kathleen; Tollman, Stephen M; et al.
Abstract: Background: Understanding how depression is associated with chronic conditions and sociodemographic characteristics can inform the design and effective targeting of depression screening and care interventions. In this study, we present some of the first evidence from sub-Saharan Africa on the association between depressive symptoms and a range of chronic conditions (diabetes, HIV, hypertension, and obesity) as well as sociodemographic characteristics. Methods: A questionnaire was administered to a population-based simple random sample of 5, 059 adults aged 40 years and older in Agincourt, South Africa. Depressive symptoms were measured using a modified version of the eight-item Center for Epidemiological Studies—Depression screening tool. Diabetes was assessed using a capillary blood glucose measurement and HIV using a dried blood spot. Results: 17.0% (95% confidence interval: 15.9%–18.1%) of participants had at least three depressive symptoms. None of the chronic conditions were significantly associated with depressive symptoms in multivariable regressions. Older age was the strongest correlate of depressive symptoms with those aged 80 years and older having on average 0.63 (95% confidence interval: 0.40–0.86; p < .001) more depressive symptoms than those aged 40–49 years. Household wealth quintile and education were not significant correlates. Conclusions: This study provides some evidence that the positive associations of depression with diabetes, HIV, hypertension, and obesity that are commonly reported in high-income settings might not exist in rural South Africa. Our finding that increasing age is strongly associated with depressive symptoms suggests that there is a particularly high need for depression screening and treatment among the elderly adults in rural South Africa.